2019
DOI: 10.5946/ce.2019.056
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Enhanced Endoscopic Ultrasound Imaging for Gastrointestinal Subepithelial Tumors

Abstract: Subepithelial tumors are divided into benign subepithelial and potentially malignant gastrointestinal stromal tumors. It is difficult to distinguish between these tumor types. Contrast-enhanced harmonic endoscopic ultrasound is reportedly useful for diagnosing subepithelial tumors, can be safely and easily performed by understanding the principle and method, and can be used to distinguish between tumor types with high sensitivity on the basis of differences in contrast effect. The generated image shows a hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Supporting evidence and comments. The numbers of patients in the studies reporting the usefulness of CH-EUS for characterization of subepithelial lesions in the upper digestive tract were small, and therefore, the confidence in the estimate of the effect is limited (Sakamoto et al 2011;Kannengiesser et al 2012;Yamashita et al 2015a;Zhao et al 2016;Kamata et al 2017;Ignee et al 2017;Tamura and Kitano, 2019;Tang et al 2019). There were four reports on CH-EUS for the differential diagnosis between lowgrade malignancy and high-grade malignancy gastrointestinal stromal tumors (GISTs) (Sakamoto et al 2011;Yamashita et al 2015a;Park et al 2016;Zhao et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Supporting evidence and comments. The numbers of patients in the studies reporting the usefulness of CH-EUS for characterization of subepithelial lesions in the upper digestive tract were small, and therefore, the confidence in the estimate of the effect is limited (Sakamoto et al 2011;Kannengiesser et al 2012;Yamashita et al 2015a;Zhao et al 2016;Kamata et al 2017;Ignee et al 2017;Tamura and Kitano, 2019;Tang et al 2019). There were four reports on CH-EUS for the differential diagnosis between lowgrade malignancy and high-grade malignancy gastrointestinal stromal tumors (GISTs) (Sakamoto et al 2011;Yamashita et al 2015a;Park et al 2016;Zhao et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies revealed that CE-EUS is useful for distinguishing between GISTs and benign SELs. Hyperenhancement is suggestive of GISTs with 78–100% sensitivity, 60–100% specificity, and 60–100% accuracy, whereas hypoenhancement is associated with leiomyomas [ 64 , 65 , 66 , 67 ]. In addition, a meta-analysis showed that CE-EUS discriminated GISTs from benign SELs with pooled sensitivity and specificity 89% (95% CI 0.82–0.93) and 82% (95% CI 0.66–0.92), respectively [ 68 ].…”
Section: New Diagnostic Modalities Of Eus Without Biopsymentioning
confidence: 99%
“…Perforation or bleeding is sometimes an inevitable complication even in the hands of an expert endoscopist. Some measures should be taken during the procedure to prevent massive bleeding such as pre-operative surveillance of the blood vessel flow by contrast-enhanced EUS 34 ; during the procedure, minute or larger vessels should be directly coagulated to prevent blind endoscopic manipulation; flushing of icy saline solution containing norepinephrine and APC or hot biopsy forceps can be used to stop the bleeding and metal clips can be applied to occlude vessels. During ET, such as resection that does not involve full mucosal thickness resection, avoidance of perforation must be solicited.…”
Section: B)mentioning
confidence: 99%